Post-mastectomy Breast Reconstruction with Autologous Tissue: Current Methods and Techniques. Issue 2 (February 2021) - Garza, Ramon; Ochoa, Oscar; Chrysopoulo, Minas
Abstract : Summary: Breast reconstruction is an option that should be considered for any patient facing a mastectomy. Autologous breast reconstruction provides the benefits of excellent longterm results, natural appearance, natural feel, and the best opportunity for sensory restoration. These factors lead many patients to choose autologous tissue over implant-based reconstruction. With improved anatomic and technical knowledge, the donor site morbidity previously associated with abdominally based autologous reconstruction has been significantly reduced. Today, the DIEP flap is the preferred autologous method allowing restoration of a "natural, " aesthetic breast with potential for sensation while simultaneously minimizing abdominal donor site morbidity. Alternative flaps and adjunctive procedures provide options when dealing with patients who present with challenging clinical scenarios because of an inadequate abdominal donor site. This paper reviews current methods employed by a high volume breast reconstruction practice to achieve these goals.